2016
DOI: 10.36834/cmej.36777
|View full text |Cite
|
Sign up to set email alerts
|

Systems 1 and 2 thinking processes and cognitive reflection testing in medical students

Abstract: Background: Diagnostic decision-making is made through a combination of Systems 1 (intuition or pattern-recognition) and Systems 2 (analytic) thinking. The purpose of this study was to use the Cognitive Reflection Test (CRT) to evaluate and compare the level of Systems 1 and 2 thinking among medical students in pre-clinical and clinical programs.Methods: The CRT is a three-question test designed to measure the ability of respondents to activate metacognitive processes and switch to System 2 (analytic) thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 18 publications
(18 reference statements)
0
59
0
Order By: Relevance
“…The OMP model was initially described in 1992 by Neher and colleagues as a method to efficiently balance teaching while simultaneously providing effective patient care. 84 This model is particularly well-suited for the busy ED environment. The OMP is a learner-centered model of instruction that is based on five microskills, as described in Table 4.…”
Section: One-minute Preceptor (Omp)mentioning
confidence: 99%
“…The OMP model was initially described in 1992 by Neher and colleagues as a method to efficiently balance teaching while simultaneously providing effective patient care. 84 This model is particularly well-suited for the busy ED environment. The OMP is a learner-centered model of instruction that is based on five microskills, as described in Table 4.…”
Section: One-minute Preceptor (Omp)mentioning
confidence: 99%
“…Almost all surgeons were completely intuitive in their thinking style, which could be potentially favourable in their day-to-day working environment, where quick, multiple and important decisions are made on ward rounds, outpatient clinics and theatre operating rooms. Indeed, undergraduate medical school teaching may encourage such thinking processes; previous reported work on 128 medical students who completed the CRT found that, compared with senior medical students, preclinical students displayed higher levels of slow, rational type 2 thinking [29]. The higher levels of conscientiousness and emotional stability reported in this group of surgeons alongside low alexithymia challenge the perceived 'surgical personality' stereotype of arrogance, impatience, extraversion and being unfriendly and distant [30].…”
Section: Discussionmentioning
confidence: 80%
“…by using system 2 thinking, which is more methodical and slower than system 1 thinking, which is faster and more imitative). 34 Although beyond the remit of this study, further research is important to establish whether such variation in LRD ability is in any way linked to laterality errors and adverse patient events.…”
Section: Adaptive Strategiesmentioning
confidence: 95%